Analysis of The Completeness of The Contents of Inpatient Medical Record Documents for Kidney Failure Cases at Ny.R.A Habibie Kidney Specialty Hospital - Raihan Nur Nabilah; Imam Rosadi (Journal of Multidisciplinary Sustainability Asean, 2024)
Background. This study aims to determine the completeness of medical record documents for inpatient cases of kidney failure because there are incompleteness in filling out the completeness of medical record documents for inpatient cases of kidney failure at the Ny.R.A Habibie Purpose. Medical records are files that contain information about patient identity, anamnese, physical laboratory determinations, diagnoses for all medical services and actions provided to patients and treatment for both inpatients, outpatients and those who get emergency services Method. Research methodology is a systematic framework or approach used by researchers use to plan, conduct, and analyze research Results. Based on the results of research that has been conducted at the Medical Records Installation at the Ny.R.A Habibie Kidney Special Hospital Bandung Conclusion. Medical record documents, in analyzing medical record files should be carried out by medical record officersThe tax system does not have a partially significant effect on taxpayers' perceptions of tax evasion because whether the tax system is good or not is not the only thing that affects the perception of taxpayers.